La enfermería en Colombia y la reforma del sector salud (1999)
ABSTRACT: A qualitative research was conducted to analyze the practice of nursing in Colombia. It seeks to understand the social value of nursing, by means of surveys to both professionals and assistants, who work in health institutions which have developed the process of reform implementation at a large scale. The nursing experience is presented from the interviewees subjective point of view, regarding what they do in general, what they know, and what they do within the context in which they work. The nature of the project does not allow generalizations, but it does identify trends in nursing practice. The research project verified that the working conditions are precarious, and that there is a distance between the professional care- taker and the subject of such attention, role idealization, ethical dilemmas, conceptual emptiness when the essence of the task has to be precised, psychological suffering, and service bureaucratization. It is a multicentric work case study guided by the PAHO, carried out in Argentina, Colombia, Brazil, Mexico, and the United States, where Nursing regulations training were also studied.